A dusty magnetospheric stream as the physical mechanism responsible for stellar occultations: Interpretation of the TESS light curve of the pre-transitional disk system UX Tau A - Nagel, Erick; Bouvier, Jerome (Astronomy and astrophysics (Berlin), 2025)
Context . Recent observations of the object UX Tau A containing a pre-transitional disk suggest that the inner disk is misaligned and precessing with respect to the outer disk. These motions lead to a highly dynamic environment that changes the reservoir of dust feeding the star. One of the effects of this is seen in the features of the Transiting Exoplanet Survey Satellite (TESS) optical light curve (LC), resembling dips of variable depth changing within the timescale of the inner disk dust replenishment. Aims . For this work we interpreted the TESS LC corresponding to a time window around the date a spectrum was taken with the James Webb Space Telescope (JWST). The spectrum was taken in the mid-infrared, clearly a range tracing the emission of dust. Compared with previous spectra, the most recent spectrum suggests a strong decrease in the amount of dust in the inner disk; the observed spectral energy distribution shows a very small infrared excess. Methods . The physical modeled flux comes from stellar radiation occulted by a sheet of evaporating dust following the magnetospheric field ( B ⋆ ) lines. A grid of stream configurations were taken where the gas component explains the JWST spectrum and the H α profiles. Results . Our quest to find a reasonable interpretation of the LC requires a tuning of the values associated with the truncation radius, the inclination of the disk with respect to the line of sight and the maximum size of the dusty grains. Conclusions . We conclude that the dust evaporation accretion flow is able to explain the typical depths of the LC features periodically changing with the stellar rotational period. We conclude that the dust evaporation accretion flow is able to explain the dips observed in the UX Tau A TESS light curve, most notably the large amplitude dips up to Δ mag ∼ 0.7 mag, while the lower level variability events (Δ mag ≤ 0.2 mag) in the LC could also be accounted for by the periodic modulation caused by a hot surface spot. We also suggest that winds and warps are unlikely mechanisms for UX Tau A’s variability.